e me l'ovrare appaga Papiri e saggi in onore di Gabriella Messeri (P.Messeri) - Bastianini, Guido; Maltomini, Francesca; Manetti, Daniela; MINUTOLI, Diletta; Pintaudi, Rosario (Edizioni dell'Istituto Papirologico «G. Vitelli», 2020)
The volume brings together contributions by many scholars, from Italy and abroad, in honour of Gabriella Messeri, who for many years was full professor of Papyrology at the "Federico II" University of Naples. The first part contains the editio princeps of 23 literary papyri (by well-known and anonymous authors) and 27 documentary papyri (administrative accounts, contracts, private letters, etc.); the second part consists of 12 essays on historical, philological and literary subjects.